PENILAIAN KINERJA TU (TATA USAHA) UNIVERSITAS ISLAM LAMONGAN - Nur Nafiiyah (Joutica, 2017)
The performance assessment of administration staff in the college did in order to improve the quality of the service process and internal continuous quality improvement. This study aims at the development of information systems web-based performance assessment. This system was built using the programming language PHP (Hypertext Processor) and MySql database, which is expected to provide a more efficient and effective in conducting this evaluation, all the colleges are trying to have an information system that not only presents a variety of important information, but also can perform the data processing. Assessmentof the performance is measurements made on various activities with the questioner. The results of the study give a rank of accumulation is obtained by calculating the second component of the assessment, the results of this can be seen anyone to find the highest rank to lowest. It is hoping that every values obtained can push Employees the administration in Lamongan Islamic university to improve its performance.